Safety and Tolerability of SBRT after High-Dose External Beam Radiation to the Lung - Owen, Dawn; Olivier, Kenneth R.; Song, Limin; Mayo, Charles S.; Miller, Robert C.; Nelson, Kathryn; Bauer, Heather; Brown, Paul D.; Park, Sean S.; Ma, Daniel J.; Garces, Yolanda I. (Frontiers in Oncology, 2015)
Purpose: Stereotactic body radiotherapy (SBRT) is commonly used to treat unresectable lung nodules. Given its relative safety and effective local control, SBRT has also been used to treat recurrent lung nodules after high dose external beam radiation (EBRT) to the lung. The toxicity of such treatment is unknown. Methods & Materials: Between 2006 and 2012, 18 subjects at the Mayo Clinic with 27 recurrent lung nodules were treated with SBRT after receiving EBRT to the lung. Median local control, overall survival, and progression free survival were described. Acute toxicity and late toxicity (defined as toxicity >= or > 90 days, respectively) were reported and graded as per standardized CTCAE 4.0 criteria. Results: The median age of patients treated was 68 years. 15 patients had recurrent lung cancer as their primary histology. 12 patients received ≥60 Gy of conventional EBRT prior to SBRT. SBRT dose and fractionation varied; the most common prescriptions were 48 Gy/4 fractions, 54 Gy/3 fractions, and 50 Gy/5 fractions. Only 4 patients had SBRT PTVs that overlapped more than 50% of their prior EBRT planning target volumes. Two patients developed local recurrence following SBRT. With a median follow up of 21.2 months, median SBRT specific overall survival and progression free survival were 21.7 months and 12.3 months respectively. No grade ≥ 3 acute or late toxicities were noted. Conclusion: SBRT may be a good salvage option for select patients with recurrent lung nodules following definitive EBRT to the chest. Toxicity is minimal and local control is excellent.